Trinuclear Diamagnetic Nickel(II) Complexes with Bridging 3‐Arylpyrazolato Ligands. Issue 35 (31st October 2013) - Salih, Kifah S. M.; Bergner, Susann; Kelm, Harald; Sun, Yu; Grün, Anneken; Schmitt, Yvonne; Schoch, Roland; Busch, Mark; Deibel, Naina; Bräse, Stefan; Sarkar, Biprajit; Bauer, Matthias; et al.
Abstract: Orange‐red trinuclear nickel(II) complexes are obtained by reacting Ni(ClO4 )2 (H2 O)6 with 3(5)‐arylpyrazoles in the presence of a base. Herein, the diamagnetic nickel centers are coordinated in a square‐pyramidal manner by four pyrazolato ligands, each of which bridges two nickel sites. The structurally unique complexes were investigated by NMR, IR, fluorescence, and X‐ray spectroscopy. All seven compounds described here were structurally elucidated by single‐crystal X‐ray diffraction. With 3(5)‐ferrocenylpyrazole as the substrate, a nonametallic system that possesses six redox‐active ferrocenyl moieties was obtained. Abstract : The reactions of Ni(ClO4 )2 (H2 O)6 with 3(5)‐arylpyrazoles in the presence of a base lead to pyrazolate‐bridged trinuclear nickel(II) complexes. This strategy allows the introduction of a broad variety of aromatic substituents such as redox‐active sites or additional phosphine donors in the periphery of the trinuclear core.